Distribution of Dental Diseases and Treatment Delivered amongst Patients Visiting Dental Outpatient Department at Gandaki Medical College, Nepal - Tuladhar, S L; Parajuli, U; Manandhar, P; Subedi, N; Kunwar, D (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: A study of dental diseases amongst patients attending dental outpatient department (OPD) helps us plan a preventive, and/or a definitive dental treatment. Objectives: To find out the distribution of dental diseases amongst patients visiting dental OPD at College of Dental Surgery, Gandaki Medical College (GMC), Pokhara, Nepal. Methods: The present study was a hospital based cross sectional descriptive study carried out during a period of one year extending from 1st February 2016 to 31st January 2017. A total of 3052 patients attending the dental OPD were included in the study. The distribution of dental diseases according to sex, age and diagnosis were collected and analyzed. Additionally, frequency distribution of treatments provided to the patients was observed. Results: Dental caries was the most prevalent dental disease (64.41%) followed by gingivitis (13.04%). The prevalence of dental caries was significantly higher in females (Females 56.91% vs. males 43.08%, P <0.05). Conversely, the prevalence of maxillofacial injuries (85.06%), dental impactions (72%), and malocclusion (53.88%) were significantly more common in male patients (P <0.05). The age group <19 years comprised 23.98 % of patients who visited the dental OPD, and the dental caries was most prevalent (27.10%) in the age group. The order of more frequent dental treatments was root canal treatment (18.84%), tooth extraction (18.44%), dental restoration (10.48%), and scaling (9.20%). Conclusions: The most prevalent dental disease was dental caries and it was more prevalent in females than in males. The most common age group reporting to Dental OPD was <19 years. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 29-32